Asuntos tratados en la Sexagésima Novena Reunión Ordinaria del Comité de Agricultura de la Organización Mundial del Comercio (OMC) - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The purpose of this note, prepared by the Center for Strategic Analysis for Agriculture (CAESPA) of the Inter-American Institute for Cooperation on Agriculture (IICA), is to inform IICA staff of the main points raised at the Sixty-ninth Regular Meeting of the WTO Committee on Agriculture, held on March 26 in Geneva, Switzerland. IICA took part in the meeting in its capacity as an observer member of the Committee.